Physiological Response, Growth, and Yield of Edamame Soybean (Glycine Max L. Merr.) Under Foliar Application of Nano Cattle Bone Ash in Entisol - Siti Maulidayanti; Didik Indradewa; Eko Hanuddin (PLANTA TROPIKA, 2023)
Nano cattle bone ash can reduce requirement for SP-36 and increase pod yield. This study aimed to examine the physiological response, growth, and yield of edamame soybean in entisol of concentration and frequency of foliar application of nano cattle bone ash and SP-36 fertilizer.The research was conducted an experimental method which arranged in a Randomized Completely Block Design (RCBD) which consists of factor concentration (0.15, 0.30, and 0.45%) and frequency (2, 3, and 4 times). In control treatment was given 100% recommended dose SP-36, whereas between concentration and frequency foliar were given 50%. The findings demonstrated that foliar application of nano cattle bone ash with 50% SP-36 resulted in higher leaf dry weight and pod yield per plant as compared to control, increasing pod production per plant by 21.7%. The results of this study concluded that nano cattle bone ash can replace a half dose of SP-36 and increase pod yield. In the future, it is expected that the use of nano cattle bone ash can be applied into soybean cultivation and reduce use of SP-36 fertilizer.